If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(v + 5) = -3(3v + -7) + 2v Reorder the terms: 5(5 + v) = -3(3v + -7) + 2v (5 * 5 + v * 5) = -3(3v + -7) + 2v (25 + 5v) = -3(3v + -7) + 2v Reorder the terms: 25 + 5v = -3(-7 + 3v) + 2v 25 + 5v = (-7 * -3 + 3v * -3) + 2v 25 + 5v = (21 + -9v) + 2v Combine like terms: -9v + 2v = -7v 25 + 5v = 21 + -7v Solving 25 + 5v = 21 + -7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7v' to each side of the equation. 25 + 5v + 7v = 21 + -7v + 7v Combine like terms: 5v + 7v = 12v 25 + 12v = 21 + -7v + 7v Combine like terms: -7v + 7v = 0 25 + 12v = 21 + 0 25 + 12v = 21 Add '-25' to each side of the equation. 25 + -25 + 12v = 21 + -25 Combine like terms: 25 + -25 = 0 0 + 12v = 21 + -25 12v = 21 + -25 Combine like terms: 21 + -25 = -4 12v = -4 Divide each side by '12'. v = -0.3333333333 Simplifying v = -0.3333333333
| 3x+1=11x-4 | | 2x+(2*3x+5)=945 | | 7(2n+4)=9(4n+5)+7 | | 4d^2-2d=0 | | 4/5x=32 | | -3x+4=4x-17 | | 6(x-2)/9=4(x+1)/12 | | 7(x+1)+7=2x+5(3+x) | | -9+12x+13k-5x-2k-25= | | 5x-3=-3x+1 | | -19=5t | | -9(x-10)=17-8x | | 3x+(2*3x+5)=945 | | 6x-(7x+6)=4x-26 | | y=3.2x+0.7 | | 1.50x+2.00=20 | | 14=-7u | | 6y+2(y-9)=6(y+1)-3 | | x-5x-60-x-13=-17 | | 7(2n+5)=8(6n+1)+6 | | k(2k+2)-6(2k+4)=k(2k-4)+(6k+9) | | -30/6= | | x+12=2x+3+9(x-3) | | 3(x-4)-8=-5(-5x+2)-8x | | 15x+21=4(3x+6)+3x-3 | | 9+36/3^2 | | 5(x-3)=2(x+9) | | 3x-5=12x-18 | | 5(y+8)+y=3(y+4)-8 | | 8x+2=8(x-1) | | 2x-7(x+9)=11 | | 9(w+6)=-8w+3 |